POTRET STUDI ALQURAN DI MATA ORIENTALIS - Ahmad Said, Hasani (Department of Alquran Science and Interpretation of the Faculty of Ushuluddin, Adab, and Dawah of IAIN Langsa, 2018)
Before the mid-19th century, most of the books written by western people attacked Islam based on purely theological reasons of Christian dogma. Through the study of Orientalism, the West tries to understand Islam in order to destroy it from the inside and thwart every effort to revive Islamic civilization. It sounds provocative, but that is the reality. Orientalist asks Omar Ibn Khattab who fear the verse of Holy Quran lost, after large number of memorizer of Holy Quran died in the war of Yamama. The Evidence of the anxiety shown with insisting Abu Bakr as a Caliph to instantly codify the Quran. In addition, for example, why the writings that shaped suhoof is not directly saved by the prophet himself, and why did the Zayd Ibn Thabit which was appointed as a codification writer of the Quran seemed unprepared with the loss of some verses from surah Baraah. Then this paper is to answer the debate in the sight of orientalists.